Improving food safety compliance of potential employees through a novel model of knowledge, attitude, commitment, and practice - Taha, Sadi; Angor, Malak; Al‐Marazeeq, Khaled M.; Osaili, Tareq M.; Albloush, Ahmad; Al‐Rousan, Walid M.; Ajo, Radwan; Holley, Richard; Fadhel, Arif; Alboqai, Omar (Journal of food science, 2024)
The global burden of foodborne illnesses remains high due to consumption of contaminated food. Vigilant attention from all, particularly food handlers, is needed to address food safety concerns and minimize the risks that affect consumer health, international business, and tourism worldwide. The main objectives of this study were to: (i) evaluate the food safety knowledge, attitudes, commitment (involving affective, continuance, and normative types), and practices of students studying subjects related to food sciences in Jordanian universities and (ii) examine the impact of knowledge and attitude on commitment, and subsequently, on relevant practices using structural equation modeling. The questionnaire was completed by 526 students from 5 universities. The score percentages of students in tested categories were as follows: agreement on food safety knowledge (87.7%), attitude (92%), affective commitment (90.4%), continuance commitment (83%), normative commitment (90.3%), and practices (91.5%). The results showed that associations between food safety knowledge and attitude with the three types of commitment were positive and significant (p < 0.05). Affective and normative commitments acted as partial mediators between food safety knowledge and practices and between food safety attitude and practices, whereas continuance commitment did not act as a mediator. Furthermore, a moderate correlation was found between food safety knowledge and attitude. Focus on food safety commitment drivers is essential, as commitment plays a key role in achieving actual hygienic practices by translating adequate knowledge and positive attitudes to improvements in hygienic behavior and reductions in the risk of foodborne illnesses.